Botanical Awareness and Adolescent Maturation in Siri Pettersen’s Odin’s Child - Irene Bordignon (Plant Perspectives)
This article supports the thesis that (eco)fantasy novels written for young adult people are nowadays crucial to give the next generation an ecological expertise to face environmental challenges. It is therefore important to consider what perceptions of nature are actually conveyed through the reading of these literary works, thus involving a pure dissemination of knowledge about flora. The novel Odin’s Child (Odinsbarn, 2013) by Siri Pettersen is considered here, giving voice to arboreal and botanical perspectives and basing the analysis on phytocriticism and the recent developments in ecocriticism. Odin’s Child supports the belief that a deep knowledge about botanical elements can be shared through the practice of embodiment and through an active interaction with the plant world, especially at a young age; for this reason, the importance of liminality and the role of contemporary literature in the human maturation process are underlined here. Plants play multiple sustainable roles in our life and for the survival of the planet: they are sources of medical treatments, and absorbers of carbon dioxide and other air pollutants (Jones and MacLeod 2022). Yet, it is only recently that scholars from the humanities have started analysing the role of plants in fiction, inaugurating the so-called ‘plant-turn’. The aim of this study is to highlight the importance of plants and botanical knowledge in young people’s understanding of and engagement with the natural world via young adult literature. This article’s approach will underscore the pedagogical value of ecofantasy as a suitable genre in creating empathy and a positive attunement towards flora in young readers. The central part of this paper, informed by the work of John C. Ryan (2018) and his phytocritical method, provides an analysis of the botanical elements of the econovel Odin’s Child, with an emphasis on its affective potential. A final reflection will involve new materialistic visions – such as the concepts of hybridisation (Curry 2013) and transcorporeality (Alaimo 2010) – in considering the liminal space of human/non-human and the girl/woman maturation process through which the novel develops.